Novitect; a novelty detection soft-computing algorithm for Structural Health Monitoring (SHM) system - Mustapha, Faizal; Abang Abdul Majid, Dayang Laila; Ng, Kooi Huat

(untitled)
In view of the criticality of structural integrity, there are many approaches and structural health monitoring techniques developed to detect damage or crack in engineering structures. This paper aims to develop Novitect, a soft computing platform system for Structural Health Monitoring (SHM). Novitect is developed using MATLAB 2008-Graphical User Interface (GUIDE) module. This system allows users to calculate the novelty index and to display the novelty index plot by processing the generated ultrasonic guided waveform response data induced in a structure. Data of hollow cylinder-like structure is presented in this paper.Novitect is designed to use novelty detection method. Novelty detection method is a multivariate statistical technique used for damage identification based on the acquired waveform response via a smart PZT sensor. The validation of the developed soft computing platform was done by comparing the works done by Mustapha et.al [1] on the hollow cylinder like structure. The developed SHM software can be served as the in-service SHM maintenance tool.